Heart-Lung Endurance Evaluation of Calisthenics Instructors from The Physical, Health and Recreation Education Department of The Faculty of Teacher Training and Education of Syiah Kuala University - Syamsulrizal Syamsulrizal; Yeni Marlina; Muhammad Iqbal; Zahara Zahara (Proceedings of AICS - Social Sciences, 2021)
Heart-lung endurance, more commonly referred to as cardiorespiratory, is the capabilities of the heart and lungs in supplying oxygen to move muscles for a considerable duration. Most calisthenics activities take up a significant duration of time, which requires the instructors to have good heart-lung endurance. Continuation exercises could positively improve the endurance of the heart and lungs and be more resilient to fatigues. The instructors continuously perform at least 5 calisthenics sessions for a duration of 30 minutes. The aim of this study is to find the existence of heart-lung endurance of calisthenics instructors from the Physical, Health, and Recreation department of the faculty of teacher training and education of Syiah Kuala University. This study utilizes a descriptive method with a quantitative approach. The population of this study is the entirety of the calisthenics instructors of the Physical, Health, and Recreation department of the Faculty of Education of Syiah Kuala Unversity, totaling 11 people. The sample was selected through a total sampling method. The data was collected using a heart-lung endurance test via a 15 minutes running test (balke test). Based on the analyzed data it could be concluded that the average energy of the female instructors’ lungs was 49.75 ml/kg/min and the male instructor was 52.41 ml/kg/min, detailing (1) 9 female instructors, with a percentage of 90%, reached the highest score and were categorized as ‘good’, and (2) the sole male instructor, 100% of the sample, reached the highest score of the ‘average’ category. The result of the study showed that most athletes were able to effectively maintain and improve their heart-lung endurance, while some needed to improve them through continuous exercise.Keywords:Heart-Lung Endurance, Calisthenics Instructor.